Purchase Intention Towards Ready-Made and Custom-Made Products in Textile and Apparel Industry - Ng, Shi Jie (2019)
An unprecedented change of consumer demand in the Malaysian textile and apparel industry has been an economic impact to various corresponding businesses. Accordingly, “the change” is believed to be the cause that turns the Malaysian industry up-side-down as the consumers decrease their spending on the textile goods extensively ever since the days of the implementation of GST (good and service tax) until today. The objective of this study is to determine the factors which are affecting the Malaysian purchase intention between the ready-made and the custom-made products in the local textile and apparel industry. Nonetheless, the proposed study would discuss the possibilities of outcomes with a series of quantitative measurements and procedures. Moreover, 151 questionnaires were collected and accepted based on the non-probability quota sampling method as the fundamental guideline for this preliminary analysis. The results suggested that there is a significant relationship between the variable name Product Safety and Convenience towards Consumer Satisfaction. Together with, there is also a proven relationship between Attitude and Consumer Satisfaction with Purchase Intention towards ready-made and custom-made products in the Malaysian textile and appeal industry.